DETERMINANTS OF FOREIGN DIRECT INVESTMENT IN INDONESIA (2019-2024) - Budiman, Antonius; Deliberto, Felicio; Wijaya, Lione; Huda, Aulia (FEB Universitas Sultan Ageng Tirtayasa, 2025)
This study examines the determinants of Foreign Direct Investment (FDI) in Indonesia from 2019 to 2024 when COVID-19 was in the intersection - using a quantitative approach and the Vector Error Correction Model (VECM) methodology. The analysis focuses on macroeconomic variables, including Gross Domestic Product (GDP), inflation, interest rates, exchange rates, Human Development Index (HDI), export levels, and Global Economic Policy Uncertainty (GEPU), assessing their short-term and long-term effects on FDI inflows. The findings reveal that in the short term, inflation, exchange rates, and GEPU do not significantly impact FDI. However, in the long term, GDP and HDI exhibit a positive and significant influence on FDI inflows, while interest rates and export levels demonstrate a significant negative effect. These results underscore the critical role of macroeconomic stability, human capital development, and coherent investment policies in attracting and sustaining FDI in Indonesia during the economic recovery phase. The study offers strategic insights for policymakers to optimize Indonesia’s investment climate amid global economic uncertainties.